Resources of Islamic Countries - Fahmi Amhar; Eka Cahya Prima (Islamic Research, 2023)
This study examines the potential outcomes of uniting the resources of Muslim countries. Despite the challenges in obtaining accurate data, various representative approaches are proposed. Among the institutions that collect such data is the Statistical, Economic and Social Research and Training Center for Islamic Countries (SESRIC), which is under the Organization of Islamic Cooperation. The analysis focuses on the sufficiency of energy, food, and industrial raw materials in Muslim nations. However, it emphasizes the need for adjustments to improve economic interdependence among these countries, reducing their reliance on developed nations that once colonized them. Furthermore, the study acknowledges the ongoing work required to tap into intangible resources effectively. The findings underscore the anticipated benefits and ease that can be achieved through collaborative efforts among Muslim countries, paving the way for improved resource utilization and collective advancement.